Pengaruh Belajar Mandiri (Self Directed Learning) dan Penggunaan Internet Sebagai Sumber Belajar terhadap Prestasi Belajar Ekonomi Siswa SMA Negeri di Kecamatan Boyolali - Elsi Putri Handayani; Mintasih Indriayu; Dini Octoria (Journal on Education, 2024)
This research aims to determine (1) the influence of self-directed learning on the economics learning achievement of State High School students in Boyolali District (2) the influence of using the internet as a learning resource on the economics learning achievement of State High School students in Boyolali District (3) the influence of learning independent (self-directed learning) and the use of the internet as a learning resource together on the economic learning achievement of State High School students in Boyolali District. The sample used in this study was 333 samples taken using proportional random sampling technique. The sample in this study were students from SMA N 1 Boyolali, SMA N 2 Boyolali, and SMA N 3 Boyolali. Data collection techniques using questionnaires and documentation of students' UTS scores. Test the validity of the instrument using product moment correlation and test reliability using Cronbach Alpha (a). The hypothesis was tested using multiple linear regression analysis using SPSS 26 software. The results of the research prove that (1) there is a positive and significant influence between self-directed learning on the economic learning achievement of State High School students in Boyolali District (2) there is a positive and significant influence between the use of the internet as a learning resource on the economic learning achievement of high school students In Boyolali District (3) there is a positive and significant influence between self-directed learning and the use of the internet as a joint learning resource on the economic learning achievement of State High School students in Boyolali District.